2021
DOI: 10.1038/s41467-021-22573-7
|View full text |Cite
|
Sign up to set email alerts
|

Higher gametocyte production and mosquito infectivity in chronic compared to incident Plasmodium falciparum infections

Abstract: Plasmodium falciparum gametocyte kinetics and infectivity may differ between chronic and incident infections. In the current study, we assess parasite kinetics and infectivity to mosquitoes among children (aged 5–10 years) from Burkina Faso with (a) incident infections following parasite clearance (n = 48) and (b) chronic asymptomatic infections (n = 60). In the incident infection cohort, 92% (44/48) of children develop symptoms within 35 days, compared to 23% (14/60) in the chronic cohort. All individuals wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 76 publications
0
68
0
Order By: Relevance
“…Gametocyte infectiousness was lower among gametocyte carriers with confirmed fever (T≥37.5°C) at the moment of mosquito feeding, as shown elsewhere. 32 This apparent decrease in mosquito infection rates has been associated with cytokine-mediated inactivation of gametocytes. 9…”
Section: Discussionmentioning
confidence: 99%
“…Gametocyte infectiousness was lower among gametocyte carriers with confirmed fever (T≥37.5°C) at the moment of mosquito feeding, as shown elsewhere. 32 This apparent decrease in mosquito infection rates has been associated with cytokine-mediated inactivation of gametocytes. 9…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Western Kenya, in an area of high malaria transmission, revealed that asymptomatic infections were responsible for 94.6% of malaria transmission [ 9 ]. Even though in low transmission areas asymptomatic low-density parasite infections are associated with lower gametocyte densities [ 14 ], they still contribute to malaria transmission [ 10 , 13 , 15 , 16 ]. Studies in Vietnam and Lao-PDR have provided evidence of persisting and oscillating submicroscopic malaria infections that frequently led to high-density infections, thus sustaining malaria transmission [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…With frequent recrudescence, human malaria infection persists for several months or years and serves as a major reservoir for malaria transmission ( Okell et al, 2012 ; Churcher et al, 2015 ; Lin et al, 2016 ; Slater et al, 2019 ; Barry et al, 2021 ). If our finding that innate immune responses were critical for the control of parasite recrudescence could be confirmed in human malaria, it will help us to design novel strategy to control parasite recrudescence and to block malaria transmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, some parasite clones are able to evade the host immune attack by switching their variant antigens, such as var , repetitive interspersed family ( rif ), and subtelomeric variant open reading frame ( stevor ), resulting in frequent recrudescence ( Scherf et al, 2008 ). Thus, after the acute infection stage, malaria infection persists at low levels for several months or years, and this has been regarded as a reservoir for malaria transmission ( Ouedraogo et al, 2009 ; Okell et al, 2012 ; Churcher et al, 2015 ; Barry et al, 2021 ). Understanding the underlying mechanisms involved in the host control of malaria recrudescence will provide us with novel clues for designing immune intervention measures against malaria parasites and blocking malaria transmission.…”
Section: Introductionmentioning
confidence: 99%